2016
DOI: 10.1039/c6cp04977j
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding surface plasmon resonance performance enabled by templated oxide gratings

Abstract: Here we report a simple and scalable soft-lithography-based templating technology for fabricating Au-covered oxide (titania and zirconia) gratings by using DVDs as a structural template. The resulting plasmonic gratings simultaneously exhibit very high surface plasmon resonance (SPR) sensitivity (up to ∼940 nm per refractive index unit, nm per RIU) and figure of merit (FOM, up to 62.5). The effects of thermal annealing of the templated oxide gratings on their final plasmonic properties have been systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…One-dimensional (1D) metallic grating is considered as the most common grating structure to excite SPP [117][118][119][120][121][122][123], for example, optical discs were frequently employed as structural template to fabricate metallic gratings [121][122][123]. Meanwhile, the performance of an Au-covered TiO 2 gratings sensor [123] was found to be highly dependent on the thermal annealing process of the oxide grating. By tuning the annealing process, this grating-coupled SPP sensor exhibited RI sensitivity up to ∼940 nm/RIU and FoM up to 62.5 RIU −1 .…”
Section: Author Manuscriptmentioning
confidence: 99%
“…One-dimensional (1D) metallic grating is considered as the most common grating structure to excite SPP [117][118][119][120][121][122][123], for example, optical discs were frequently employed as structural template to fabricate metallic gratings [121][122][123]. Meanwhile, the performance of an Au-covered TiO 2 gratings sensor [123] was found to be highly dependent on the thermal annealing process of the oxide grating. By tuning the annealing process, this grating-coupled SPP sensor exhibited RI sensitivity up to ∼940 nm/RIU and FoM up to 62.5 RIU −1 .…”
Section: Author Manuscriptmentioning
confidence: 99%
“…The structure was used for RI sensing. Additional works on SPR based DVD structures can be found in [ 37 , 38 , 39 , 40 , 41 ]. Theoretical and experimental study of the SPR supported by CDs can be found in [ 42 ], biosensing application of different types of CDs is discussed in [ 43 ].…”
Section: Swg and Nanograting-based Sensors Configurationsmentioning
confidence: 99%
“…Many of these fabrication methods of gratings consist of several steps, which leads to a longer time required to structure fabrication. There have been presented interesting results of grating-coupled SPR sensors employing grating structures, mainly one-dimensional (1D) [ 26 , 27 , 28 , 29 , 30 , 31 ]. There is an effort to achieve grating-based sensors with high sensitivity and easy and cheap fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…There is an effort to achieve grating-based sensors with high sensitivity and easy and cheap fabrication. For this reason, many research groups used optical discs as structural template for fabrication of metallic gratings [ 26 , 28 , 32 , 33 , 34 ]. The grating-coupled SPR sensors were used as temperature sensors [ 21 ], RI sensors [ 24 , 25 , 33 , 35 ] and as biosensors [ 10 , 18 , 19 , 32 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%